2015
DOI: 10.1007/s10549-015-3512-2
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome inhibitors induce AMPK activation via CaMKKβ in human breast cancer cells

Abstract: The purpose of present study is to examine the mechanism of the 5'-AMP-activated protein kinase (AMPK) activation induced by proteasome inhibitors. AMPK activation and ubiquitin proteasome system (UPS) inhibition have gained great attention as therapeutic strategies for the treatment of certain types of cancers. While AMPK serves as a master regulator of cellular metabolism, UPS regulates protein homeostasis. However, the relationship between these two important pathways is not very clear. We observe that prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…Previous studies demonstrated that ER stress induced AMPK expression in malignancies (11,12). Furthermore, AMPK is known to act against cancer by suppressing the mTOR pathway (13).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies demonstrated that ER stress induced AMPK expression in malignancies (11,12). Furthermore, AMPK is known to act against cancer by suppressing the mTOR pathway (13).…”
Section: Resultsmentioning
confidence: 98%
“…ER stress induction can also trigger AMPK activation by decreasing cellular ATP levels (27,28). Another important mechanism of AMPK activation is regulation of the AMPK-activating calcium/calmodulin-dependent kinase kinase (CaMKK)-beta by ER stress (12,29,30). Furthermore, our previous studies revealed that ER stress induction is closely associated with AMPK activation (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps even more significant is the potential for targeting the CaMKK2/CaMKIV signaling axis by using STO-609 as a therapeutic recourse. Several studies have focused on Ca 2+ signaling components, and CaMKK2 in particular, to explore new therapeutic avenues for combatting fatty liver disease and cancer [39,40]. Baicalin, a polyphenolic compound, decreased fat, liver, and whole body weights in HFD-fed mice by inhibiting the CaMKK2-AMPK pathway [39], while bortezomib, a proteasome inhibitor and multiple myeloma therapeutic agent, activated CaMKK2 protein synthesis in human breast cancer cell lines [40].…”
Section: Tissue-specific Metabolic Regulation By the Ca2+/cam-dependementioning
confidence: 99%
“…Recent studies identified the ubiquitin proteasome system as a factor regulating AMPK activity directly and indirectly [ 54 , 55 ]. AMPK-related kinases, such as AMPK-related kinase 5 (NUAK1) and microtubule-affinity-regulating kinase 4 (MARK4), are polyubiquitinated in vivo and interact with the deubiquitinating enzyme ubiquitin specific protease-9 (USP9X).…”
Section: Amp-activated Protein Kinase: Structure and Regulationmentioning
confidence: 99%